Automobile brake pad friction and wear test rig: Fabrication / Ismail Mesror - Mesror, Ismail (2005)
This report is about development of an automobile brake pad testing machine. In this project, the most significant thing is to develop a machine that can apply load at a certain interval of time repeatedly. The scope of the project is to develop a machine that can hold an automobile brake pad material that can be operated at various speeds. The machine can also perform brake and release action and be able to operate for long hours. A few friction and wear test in wet condition are also accomplished. The design parameters are based on ‘Automobile Brake Pad Friction and Wear Test Rig: Design’ by Adam Hood Bin Ab. Rahim. In this report also, I have given some literature review about the machine, fabrication and machining process, some calculations on fabrication and machining process, technical drawings in forms of CATIA and AutoCAD, procedures in commissioning friction and wear test in wet condition and also the analysis of the data. In completion of this report, I have gathered related information from many sources such as books, websites, catalogs, lecturers and friends.